2022
DOI: 10.3390/genes13091637
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Analysis of Lactation-Related miRNA and mRNA Expression Profiles in Donkey Mammary Glands

Abstract: Donkey milk is consumed by humans for its nutritional and therapeutic properties. MicroRNAs (miRNAs) and messenger RNAs (mRNAs) have been implicated in the regulation of milk component synthesis and mammary gland development. However, the regulatory profile of the miRNAs and mRNAs involved in lactation in donkeys is unclear. We performed mRNA-seq and miRNA-seq and constructed coexpression regulatory networks for the mammary glands during the lactating and nonlactating period of jennies. We identified 3144 diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…The study proposes that these genetic variations could serve as valuable markers for selective breeding programs in donkeys [98]. Furthermore, by conducting a transcriptomic analysis, Fei et al [99] reported several genes (CSN1S2, LEPR, LTF; CSN2, CSN1S1, CSN3, LALBA, SPP1, MGP, TGFβ1, FASN, SCD, ACACA, PPARG, INS, IGF1, GH, PRL) and pathways (lactose biosynthesis, fatty acid biosynthesis, insulin signaling pathway, prolactin signaling pathway, PI3K-Akt signaling pathway, MAPK signaling pathway, TGF-beta signaling pathway, ECM-receptor interaction) that were associated with milk production phenotypic traits in donkeys [99]. The existing data published on donkey research showed that there is still very limited information are available in this area.…”
Section: Transcriptomic and Candidate Gene Approach For Screening Gen...mentioning
confidence: 99%
“…The study proposes that these genetic variations could serve as valuable markers for selective breeding programs in donkeys [98]. Furthermore, by conducting a transcriptomic analysis, Fei et al [99] reported several genes (CSN1S2, LEPR, LTF; CSN2, CSN1S1, CSN3, LALBA, SPP1, MGP, TGFβ1, FASN, SCD, ACACA, PPARG, INS, IGF1, GH, PRL) and pathways (lactose biosynthesis, fatty acid biosynthesis, insulin signaling pathway, prolactin signaling pathway, PI3K-Akt signaling pathway, MAPK signaling pathway, TGF-beta signaling pathway, ECM-receptor interaction) that were associated with milk production phenotypic traits in donkeys [99]. The existing data published on donkey research showed that there is still very limited information are available in this area.…”
Section: Transcriptomic and Candidate Gene Approach For Screening Gen...mentioning
confidence: 99%